Lucidis 124m Edof Iol; Experience from Two Tertiary Care Centers and Quality of Life Study: Doi: 10.36351/pjo.v40i1.1719 - Mazhry, Zia ul; Hassan, Faiza; Abdullah, Muhammad; Asif, Laiba (Pakistan Journal of Ophthalmology, 2023)
Purpose: To determine visual outcomes and post-operative complications after Lucidis 124M EDOF IOL implantation after phacoemulsification and to see the effect of these lenses on Quality of life of the patients. Study Design: Mixed study design (Quasi Experimentaland qualitative analysis). Place and Duration of Study: WAPDA Teaching Hospital and Acuity Eye Centre, Lahore, from November 2017 to October 2022. Methods: Hundred eyes of seventy five patients underwent Lucidis EDOF IOL implantation after phacoemulsification using 2.75 mm clear posterior corneal incisions. Criteria used to document visual outcomes were uncorrected and corrected distance and near vision measurements. Quality of life (QoL) was assessed by interviewing the patients at least 6 months postoperatively using google forms. Results: Hundred eyes of 75 patients were enrolled. There were 39 (52%) males and 36 (48%) females. Mean age was 1.48 ± 0.50 years. Meanbaseline un-corrected visual acuity (UCVA) was 2.83 ± 1.48. Eighty two percent eyes had corrected vision of 6/6 and 75 eyes achieved N.6 for near. Fifty patients out of 75 responded to the questionnaire regarding QoL. Sixteen percent patients had glare, 85% reported no difficulties during night driving and 68% had no problem in watching TV without glasses. Sixty eight percent did not experience any itching, watering, or discomfort and 90% responded that their QoL had improved. None of the patients had lens deposits, discoloration or decentration. One had endophthalmitis. Conclusion: Lucidis EDOF IOL are safe and effective lenses in terms of visual outcomes and spectacle independence resulting in better quality of life.